Literature Review: Effectiveness of Elastic Therapeutic Taping (ETT) in Reduce the Scale of Low Back Pain in the 3rd Trimester of Pregnancy: - Nesya Vanielatama; Hartanto, Hartanto; Gunardi, Santoso (Jurnal MedScientiae, 2024)
One of the physiological changes in pregnant women in the third trimester is the gradual musculoskeletal changes associated with the occurrence of low back pain due to increased body weight and changes in body posture. One of the new technologies in physical therapy is the use of elastic therapeutic bandages. This literature review aims to determine the effectiveness of elastic therapeutic taping (ett) against LBP in the third trimester of pregnancy. Of the 11 studies reviewed by the authors, it was shown that ETT support for low back pain relief was usually installed in the lumbar region 5 (L5) and sacrum (S1) with a band pattern I. ETT can be done 2 times a week and the ETT is replaced 3 days every 3 weeks for best results. optimally with a duration of 24-72 hours. ETT can reduce pain scores more significantly when combined with other therapies such as Paracetamol plus ETT, TENS plus ETT, ETT with oblique pelvic exercises, back exercises with ETT. The conclusion is that ETT can relieve low back pain and have a very real effect in reducing low back pain intensity in the last trimester of pregnancy.